If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5(2x + -11) = 53 Reorder the terms: 2x + 5(-11 + 2x) = 53 2x + (-11 * 5 + 2x * 5) = 53 2x + (-55 + 10x) = 53 Reorder the terms: -55 + 2x + 10x = 53 Combine like terms: 2x + 10x = 12x -55 + 12x = 53 Solving -55 + 12x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '55' to each side of the equation. -55 + 55 + 12x = 53 + 55 Combine like terms: -55 + 55 = 0 0 + 12x = 53 + 55 12x = 53 + 55 Combine like terms: 53 + 55 = 108 12x = 108 Divide each side by '12'. x = 9 Simplifying x = 9
| x^2+5x=64 | | 3x+40=115 | | 3x+3+5y=18 | | x/2+5=x/7+50/7 | | 8=v(v-7) | | 4x-11=5x+7 | | 1.3-0.42z+z=1.2 | | (y+1)(y-3)=5 | | 4w^2-15w=4 | | x^4-4x^3+5=0 | | -7-x/5=-10 | | solvexy+7=nfory | | 4x^3-4x^3+5=0 | | f(x)=-5x-1 | | (4x^3)-(4x^3)+5=0 | | g(x)=2x^2 | | 4a^2+25=0 | | 60x^2+80x+25=0 | | 7+3t=-20 | | 5y-6=-6+2y | | (-8-2)*-64=b | | 9z-23=-71+z | | -89+(w*-49)=793 | | 3x+6/5=4x-4 | | u-(392/-49)=-85 | | (-21*m)-10=850 | | 16x^2-8x+145=0 | | (266/-19)-m=15 | | -6*(-3+n)=30 | | 2x+29y=13 | | (3x-5)x=28 | | k*(198/-18)=462 |